High system efficiency nonlinear frequency conversion on thin-film lithium niobate - Lohmann, Philipp; Wendland, Daniel; Lenzini, Francesco; Pernice, Wolfram (Optics letters, 2025)
Integrated photonic platforms can greatly enhance the efficiency of nonlinear frequency conversion processes by tightly confining light on a sub-micron scale. However, this advantage is often reduced by large fiber-to-chip coupling losses that drastically reduce the overall performance. Here, we demonstrate a highly efficient thin-film lithium niobate (LN) frequency converter based on periodically poled waveguides combined with direct laser written out-of-plane couplers. Including on-chip and fiber-to-chip losses, we obtain a conversion efficiency of 152%/W, thus demonstrating a promising approach for future scalable integrated devices.